Binder and preparation method thereof, positive electrode slurry, positive electrode plate and sodium ion battery
By preparing a new type of binder with polar groups, the problem of poor dispersion and adhesion of binder in sodium ion batteries is solved, and the stable dispersion of active materials and the improvement of battery performance is achieved.
Patent Information
- Application Number
- CN202510433291.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-08
- Publication Date
- 2025-07-08
AI Technical Summary
Among the existing sodium ion batteries, the adhesiveness of polyvinylidene fluoride (PVDF) adhesive is poor, which affects the electrode mechanical strength, electron conductivity and ion transmission path, and it is difficult to disperse the active materials, adhesives and conductive agents evenly, resulting in difficulty in coating and affecting the overall performance of the battery.
A new type of binder is prepared by radical polymerization. By mixing the first monomer and the second monomer, a binder backbone and branch chain with polar groups is formed, and the polar groups are used to form coordination bonds and hydrogen bonds with active material particles, combining with the steric hindrance effect to achieve stable dispersion and bonding of the active material.
The dispersion and adhesion of the adhesive are improved, the adhesion between the positive electrode active material and the current collector is improved, the mechanical and electrochemical properties of the battery are improved, and the coating difficulties are solved.
Smart Images

Figure BDA0005348837460000101
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and particularly to a binder, a preparation method thereof, a positive electrode slurry, a positive electrode sheet, and a sodium ion battery. Background Art
[0002] With the continuous development and innovation of new energy battery technologies, sodium ion batteries have become a new focus in the competition for clean energy solutions due to the advantages of sodium-based materials having high natural abundance and low production costs, which can greatly alleviate problems such as the shortage of raw materials for current lithium ion batteries and the range anxiety of lead-acid batteries.
[0003] The preparation of the positive electrode is an important link in the production process of sodium ion batteries, mainly including the stirring and coating of the positive electrode slurry. The positive electrode slurry is mainly composed of an active material, a conductive agent, a binder, and a dispersion solvent. After the binder is dissolved in the dispersion solvent, the active material and the conductive agent are combined to form a slurry, and the slurry is coated on a current collector foil and dried to form an electrode sheet. At present, polyvinylidene fluoride (PVDF) is generally used as the binder for the positive electrode slurry of sodium ion batteries, but PVDF has some problems that hinder its application: one is that the adhesion of PVDF is poor, which will affect the mechanical strength, electron conductivity, and ion transport path of the electrode; the other is that because the particle size of the active material (such as sodium iron phosphate, a polyanion material) is small and the specific surface area is large, during the homogenization process, it is difficult for the active material, the binder, and the conductive agent to be uniformly dispersed, resulting in too high viscosity or too low solid content of the slurry, and further leading to difficult coating. Moreover, the uneven distribution of the active material, the binder, and the conductive agent will also greatly affect the comprehensive performance of the battery.
[0004] Therefore, developing a new type of binder to improve the defects of poor dispersibility and poor adhesion of the binder is of great significance for the large-scale application of sodium ion batteries. Summary of the Invention
[0005] The main object of the present invention is to provide a binder, a preparation method thereof, a positive electrode slurry, a positive electrode sheet, and a sodium ion battery, aiming to solve the problems of poor dispersibility and poor adhesion of the binder for existing sodium ion batteries.
[0006] To achieve the above object, the present invention provides a preparation method of a binder, including the following steps:
[0007] Mix a first monomer, a second monomer, a solvent, and an initiator, and carry out a free radical polymerization reaction to obtain a binder; wherein:
[0008] The first monomer includes any one of styrene, methyl acrylate, butadiene, propylene, difluoroethylene, and tetrafluoropropylene, and the second monomer includes any one of tetrafluoroethylene, isobutene, vinyl ethyl ether, methyl methacrylate, methylstyrene, acrylonitrile, and hexafluoropropylene. At least one of the first monomer and the second monomer contains a polar group;
[0009] The mass ratio of the first monomer to the second monomer is (6 - 8):(2 - 4).
[0010] In one embodiment, the conditions for the radical polymerization reaction include: the temperature is 60 - 80 °C, the pressure is 3 - 8 Mpa, and the time is 8 - 10 h.
[0011] In one embodiment, the solvent includes at least one of deionized water, N,N-dimethylformamide, N-methylpyrrolidone, tetrahydrofuran, and pyridine; and / or,
[0012] The mass ratio of the first monomer to the solvent is (6 - 8):9.
[0013] In one embodiment, the initiator includes any one of azobisisobutyronitrile, benzoyl peroxide, diisopropyl peroxydicarbonate, and di-tert-butyl peroxide; and / or,
[0014] The mass ratio of the first monomer to the initiator is (6 - 8):2.
[0015] In one embodiment, the step of mixing the first monomer, the second monomer, the solvent, and the initiator and performing a radical polymerization reaction to obtain a binder includes:
[0016] Mix the first monomer, the second monomer, the solvent, and the initiator, and perform a radical polymerization reaction to obtain a slurry containing a binder;
[0017] Filter the slurry containing the binder to obtain a solid;
[0018] Wash and dry the solid to obtain a binder.
[0019] In one embodiment, the solvent for washing is hydrofluoric acid or sodium hydroxide; and / or,
[0020] The temperature for drying is 60 - 80 °C.
[0021] The present invention provides a binder, and the binder is prepared according to the preparation method of the binder described above.
[0022] The present invention provides a positive electrode slurry, and the positive electrode slurry includes the binder described above.
[0023] In one embodiment, the positive electrode paste further includes a positive electrode active material and a conductive agent, and the mass ratio of the positive electrode active material, the conductive agent, and the binder is (8.5 to 9.5):(0.3 to 2.0):(0.4 to 3.0).
[0024] The present invention provides a positive electrode sheet, which includes a positive electrode current collector and a positive electrode active layer provided on at least one surface of the positive electrode current collector, and the positive electrode active layer includes the positive electrode paste as described above.
[0025] The present invention provides a sodium ion battery, which includes the positive electrode sheet as described above.
[0026] In the technical solution of the present invention, a first monomer and a second monomer are polymerized to obtain a binder. Among them, the first monomer is the main chain of the binder, and the second monomer is the side chain of the binder. Since at least one of the first monomer and the second monomer has a polar substituent, the obtained binder can form coordination bonds, hydrogen bonds, van der Waals forces, etc. with the positive electrode active material particles in the paste through the polar groups on the long chain, so that the binder is tightly connected to the surface of the active material particles in a multi-point form, thereby improving the adhesion between the positive electrode active substance and the current collector; and because the long chain of the binder of the present invention has a strong steric hindrance effect, the positive electrode active material particles cannot approach and agglomerate, so the positive electrode active material particles can be stably dispersed in the paste; in addition, since the first monomer and the second monomer have substituents, at least one saturated bond can be formed between the two unsaturated bonds to prevent the highly active hydroxide ions in the alkaline paste from attacking adjacent unsaturated bonds and triggering a chain reaction, thereby improving chemical stability. The binder provided by the present invention can be used to improve the defects of poor dispersibility and poor adhesion of the binder, and improve the comprehensive performance of the battery. Detailed Embodiments
[0027] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts shall fall within the protection scope of the present invention.
[0028] It should be noted that if there are directional indications (such as up, down, left, right, front, back...) in the embodiments of the present invention, the directional indications are only used to explain the relative positional relationship and movement of each component in a specific posture. If the specific posture changes, the directional indications will also change accordingly.
[0029] In addition, if the descriptions such as "first" and "second" are involved in the embodiments of the present invention, the descriptions of "first", "second", etc. are only for descriptive purposes and should not be construed as indicating or implying their relative importance or implicitly indicating the quantity of the indicated technical features. Thus, the features defined with "first" and "second" may explicitly or implicitly include at least one such feature. In addition, if "and / or" or "and / or" appears throughout the text, its meaning includes three parallel scenarios. Taking "A and / or B" as an example, it includes scenario A, or scenario B, or the scenario where both A and B are satisfied simultaneously. In addition, the technical solutions between various embodiments can be combined with each other, but it must be based on the fact that those of ordinary skill in the art can implement it. When the combination of technical solutions results in contradictions or is unable to be implemented, it should be considered that such a combination of technical solutions does not exist and is not within the scope of protection required by the present invention.
[0030] The preparation of the positive electrode of a sodium-ion battery is an important link in the production and preparation process of sodium-ion batteries, mainly including the stirring and coating of the positive electrode slurry. The positive electrode slurry is mainly composed of active materials, conductive agents, binders, and dispersing solvents. After the binder is dissolved in the dispersing solvent, it combines the active materials and conductive agents to form a slurry, which is coated on the current collector foil and dried to form an electrode sheet. Currently, polyvinylidene fluoride (PVDF) is generally used as the binder for the positive electrode slurry of sodium-ion batteries, but there are some problems that hinder its application: First, the adhesiveness of polyvinylidene fluoride is poor, which will affect the mechanical strength, electron conductivity, and ion transport path of the electrode; Second, because the particle size of the active material (such as sodium iron phosphate, a polyanion material) is small and the specific surface area is large, during the homogenization process, it is difficult for the active material, binder, and conductive agent to be evenly dispersed, resulting in too high viscosity or too low solid content of the slurry, and then leading to difficult coating. Moreover, the uneven distribution of the active material, binder, and conductive agent will also greatly affect the comprehensive performance of the battery. Therefore, improving the defects of poor dispersibility and adhesiveness of the binder is of great significance for the large-scale application of sodium-ion batteries.
[0031] In view of this, the present invention proposes a preparation method for a binder, including the following steps:
[0032] Mix a first monomer, a second monomer, a solvent, and an initiator, and carry out a free radical polymerization reaction to obtain a binder; wherein:
[0033] The first monomer includes any one of styrene, methyl acrylate, butadiene, propylene, difluoroethylene, and tetrafluoropropylene, and the second monomer includes any one of tetrafluoroethylene, isobutene, vinyl ethyl ether, methyl methacrylate, methyl styrene, acrylonitrile, and hexafluoropropylene. At least one of the first monomer and the second monomer contains a polar group;
[0034] The mass ratio of the first monomer to the second monomer is (6 - 8):(2 - 4).
[0035] In the technical solution of the present invention, a binder is obtained by polymerizing the first monomer and the second monomer. Among them, the first monomer is the main chain of the binder, and the second monomer is the side chain of the binder. Since at least one of the first monomer and the second monomer has a polar substituent, the obtained binder can form coordination bonds, hydrogen bonds or van der Waals forces and other interactions with the positive electrode active material (such as sodium iron phosphate) particles in the slurry through the polar groups on the long chain, so that the binder is tightly connected to the surface of the active material particles in a multi-point form, improving the adhesion between the positive electrode active substance and the current collector; and because the long chain of the binder of the present invention has a strong steric hindrance effect, the positive electrode active material particles cannot approach and agglomerate, so the positive electrode active material particles can be stably dispersed in the slurry; in addition, since the first monomer and the second monomer have substituents, at least one saturated bond can be formed between two unsaturated bonds, preventing the highly active hydroxide ions in the alkaline slurry from attacking adjacent unsaturated bonds and triggering a chain reaction (such as over-crosslinking or degradation), thereby improving chemical stability. The binder provided by the present invention can be used to improve the defects of poor dispersibility and poor adhesion of the binder, and improve the comprehensive performance of the battery.
[0036] The technical solution of the present invention sets the mass ratio of the first monomer to the second monomer as (6 - 8):(2 - 4). If the dosage of the first monomer is too low, the purpose of improving the flexibility of the electrode sheet cannot be achieved; if the dosage of the second monomer is too high, the adhesion of the electrode sheet decreases, affecting the cycle performance of the battery. Setting the mass ratio of the first monomer to the second monomer within the above range, the material has good adhesion, flexibility and processability.
[0037] It should be noted that due to the presence of unsaturated bonds in the conventional binder and the high alkalinity of the slurry, the binder will lose dehydroxide ions, making the positive electrode slurry a jelly-like gel and deteriorating the processing performance. In the technical solution of the present invention, when the first monomer or the second monomer used contains a weakly acidic group (such as acrylic acid), it can neutralize the alkalinity in the slurry and improve the processing performance of the slurry.
[0038] In an embodiment of the present invention, the conditions for the radical polymerization reaction include: a temperature of 60 to 80 °C, a pressure of 3 to 8 Mpa, and a time of 8 to 10 h. Setting the polymerization temperature to 60 to 80 °C is conducive to the smooth and effective reaction of the first monomer and the second monomer. Within this range, the polymerization reaction temperature can be 60 °C, 65 °C, 70 °C, 75 °C, or 80 °C. Setting the polymerization reaction pressure to 3 to 8 Mpa is conducive to controlling the growth rate of the binder side chains. Within this range, the polymerization reaction pressure can be 3 Mpa, 4 Mpa, 5 Mpa, 6 Mpa, 7 Mpa, or 8 Mpa. Setting the polymerization reaction time to 8 to 10 h makes the reaction more sufficient and uniform, improving the uniformity of the product performance. Within this range, the polymerization reaction time can be 8 h, 8.5 h, 9 h, 9.5 h, or 10 h.
[0039] In an embodiment of the present invention, the weight-average molecular weight of the binder is 600,000 to 1,200,000. Herein, the "weight-average molecular weight" refers to the sum of the products of the weight fractions of molecules with different molecular weights in the polymer and their corresponding molecular weights. If the weight-average molecular weight of the binder is too large, the flexibility of the electrode sheet will be reduced; if the weight-average molecular weight is too small, it is impossible to ensure that the electrode sheet has sufficient binding force in the case of a low binder addition amount.
[0040] In an embodiment of the present invention, the Dv50 of the binder is 60 to 110 μm. Herein, "Dv50" represents the particle size that reaches 50% of the cumulative volume from the small particle size side in the particle size distribution based on volume, also known as the median particle size or mid-value particle size, and is usually used to represent the average particle size of the powder. When the particle size of the binder is set within the above range, it has good binding performance and can be evenly distributed in the slurry, which helps to improve the mechanical properties and electrochemical properties of the electrode.
[0041] In an embodiment of the present invention, the solvent includes at least one of deionized water, N,N-dimethylformamide, N-methylpyrrolidone, tetrahydrofuran, and pyridine. Preferably, the solvent is deionized water.
[0042] In an embodiment of the present invention, the mass ratio of the first monomer to the solvent is (6 to 8):9. Setting the amount of the solvent within the above range can reduce side reactions and control the reaction rate.
[0043] In the technical solution of the present invention, the initiator includes any one of azobisisobutyronitrile, benzoyl peroxide, diisopropyl peroxydicarbonate, and di-tert-butyl peroxide. In an embodiment of the present invention, azobisisobutyronitrile is selected as the initiator.
[0044] In an embodiment of the present invention, the mass ratio of the first monomer to the initiator is (6 to 8):2.
[0045] The present invention provides a binder, which is prepared according to the preparation method of the binder described in the above technical solution.
[0046] The present invention provides a positive electrode paste, which includes the binder described above. All technical solutions of the positive electrode paste include the binder, and thus have all the beneficial effects of the binder. The present invention will not elaborate on them one by one here.
[0047] In an embodiment of the present invention, the positive electrode paste further includes a positive electrode active material and a conductive agent, and the mass ratio of the positive electrode active material, the conductive agent and the binder is (8.5 - 9.5):(0.3 - 2.0):(0.4 - 3.0). The proportion of the mass ratio of the positive electrode active material, the conductive agent and the binder will affect the energy density of the battery, the conductivity of the electrode, the mechanical strength and the processing difficulty. If the dosage of the binder is too high, the binder coating layer covering the surface of the positive electrode active material will be too thick, resulting in a brittle and less ductile electrode sheet. In addition, too much binder will cause a decrease in the loading amount of the positive electrode active material in the electrode sheet, resulting in a decrease in the energy density of the battery and a reduction in the battery capacity; if the dosage of the binder is too low, the sufficient binding effect cannot be achieved, and the sufficient amount of conductive agent and positive electrode active material cannot be bonded together, and the binding force of the electrode sheet is small; it cannot be tightly combined on the surface of the active material, resulting in easy powder shedding on the surface of the electrode sheet and a decrease in the cycle performance of the battery. The technical solution of the present invention sets the mass ratio of the positive electrode active material, the conductive agent and the binder within the above range, and the performance of the battery cell is better.
[0048] In an embodiment of the present invention, the positive electrode active material can adopt the positive electrode active material known in the art for batteries. The positive electrode active material includes a doped sodium iron phosphate material, and the structural formula of the doped sodium iron phosphate material is Na4Fe 3- y M y (PO4) x (P2O7) 3-x , where M is selected from at least one of Cu, Cr, Zn, Pb, Ca, Co, Ni, Sr or Ti, 3 > x ≥ 0, 3 > y ≥ 0. The present invention selects a doped sodium iron phosphate material as the active substance. The sodium iron phosphate material has a three-dimensional framework structure, which can provide a stable crystal structure to accommodate larger-sized sodium ions and exhibits good thermal stability and safety characteristics. After introducing the transition metal M, this multi-element doping can adjust the electronic structure and sodium ion diffusion path of the material, thereby optimizing the electrochemical performance of the sodium ion battery.
[0049] In an embodiment of the present invention, the conductive agent includes at least one of carbon black, acetylene black, graphene and carbon nanotubes. In an embodiment of the present invention, carbon black is selected as the conductive agent.
[0050] In an embodiment of the present invention, the specific surface area of the positive electrode active material is 8 - 12 m 2 / g. It should be noted that the specific surface area of the positive electrode active material refers to the average value of the specific surface area of the positive electrode active material. Setting the specific surface area of the positive electrode active material to 8 - 12 m 2 / g is beneficial to improving the compaction density of the electrode sheet of the battery cell.
[0051] In an embodiment of the present invention, the average particle size distribution of the positive electrode active material satisfies: Dv10 ≥ 0.5 μm, Dv90 ≤ 25 μm, 2 μm ≤ Dv50 ≤ 9 μm, 0.1 ≤ Dv50 / (Dv90 - Dv10) ≤ 10. It should be noted that Dv10 represents the particle size at which the cumulative volume reaches 10% from the small particle size side in the particle size distribution based on volume; Dv50 represents the particle size at which the cumulative volume reaches 50% from the small particle size side in the particle size distribution based on volume, also known as the median particle size or mid-value particle size, and is usually used to represent the average particle size of the powder; Dv90 represents the particle size at which the cumulative volume reaches 90% from the small particle size side in the particle size distribution based on volume. Setting Dv10, Dv50, and Dv90 within the above ranges is beneficial to improving the rate performance and cycling performance of the battery cell of the battery.
[0052] The present invention provides a positive electrode sheet, which includes a positive electrode current collector and a positive electrode active layer provided on at least one surface of the positive electrode current collector, and the positive electrode active layer includes the positive electrode paste described above. All technical solutions of the positive electrode paste include the binder, and thus have all the beneficial effects of the binder. The present invention will not elaborate on them one by one here.
[0053] The present invention provides a sodium-ion battery, which includes the positive electrode sheet described above. All technical solutions of the sodium-ion battery include the positive electrode sheet, and thus have all the beneficial effects of the positive electrode sheet. The present invention will not elaborate on them one by one here.
[0054] The present invention provides an electrical device, which includes the sodium-ion battery described above. All technical solutions of the electrical device include the sodium-ion battery, and thus have all the beneficial effects of the sodium-ion battery. The present invention will not elaborate on them one by one here.
[0055] The technical solutions of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only used to explain the present invention and are not used to limit the present invention.
[0056] Example 1
[0057] A method for preparing a binder includes the following steps:
[0058] Add 0.8 g of styrene, 0.2 g of methyl methacrylate, 0.9 g of deionized water, and 0.2 g of azobisisobutyronitrile into an autoclave, and carry out a polymerization reaction at 60 °C and 3 Mpa for 8 h to obtain a slurry containing a binder. Sieve and centrifuge the slurry containing the binder to obtain a solid. Subsequently, wash the solid with hydrofluoric acid first, and then place it in an oven at 80 °C to dry to obtain a binder.
[0059] Example 2
[0060] Compared with Example 1, the difference is that 0.6 g of tetrafluoropropene, 0.4 g of isobutene, 0.9 g of deionized water, and 0.2 g of azobisisobutyronitrile are added into the autoclave, and a polymerization reaction is carried out at 70 °C and 5 Mpa for 9 h.
[0061] Example 3
[0062] Compared with Example 1, the difference is that 0.7 g of methyl acrylate, 0.3 g of hexafluoropropene, 0.9 g of deionized water, and 0.2 g of azobisisobutyronitrile are added into the autoclave, and a polymerization reaction is carried out at 80 °C and 8 Mpa for 10 h.
[0063] Example 4
[0064] A sodium-ion battery, wherein the sodium-ion battery uses the binder of Example 1.
[0065] The positive electrode slurry of the sodium-ion battery contains the following components by mass ratio: doped sodium iron phosphate material: conductive agent: binder = 9.0: 0.3: 0.7. The chemical general formula of the doped sodium iron phosphate material used is Na4Fe2Mn(PO4)2(P2O7). Dv10 = 0.9 μm, Dv50 = 2.5 μm, Dv90 = 13 μm, and the specific surface area is 8.5 m 2 / g.
[0066] The negative electrode material of the sodium-ion battery contains the following components by mass ratio: hard carbon: carbon black: styrene-butadiene rubber (SBR): sodium carboxymethyl cellulose (CMC) = 9.0: 0.4: 0.3: 0.3.
[0067] The N / P ratio of the sodium-ion battery is 1:1.
[0068] Example 5
[0069] Compared with Example 4, the difference is that the sodium-ion battery uses the binder of Example 2, and the following adaptive adjustments are made to the positive electrode slurry of the sodium-ion battery: the mass ratio of the doped sodium iron phosphate material, the conductive agent, and the binder is 9.2: 0.4: 0.4; Dv10 of the doped sodium iron phosphate material = 0.8 μm, Dv50 = 4 μm, Dv90 = 10 μm, and the specific surface area is 14 m2 / g.
[0070] Example 6
[0071] Compared with Example 4, the difference lies in that the sodium ion battery uses the binder of Example 3, and the following adaptive adjustments are made to the positive electrode paste of the sodium ion battery: the mass ratio of the doped sodium iron phosphate material, the conductive agent, and the binder is 9.0:0.45:0.55; the Dv10 of the doped sodium iron phosphate material used is 1.2 μm, Dv50 = 6.7 μm, Dv90 = 20.8 μm, and the specific surface area is 9.5 m 2 / g.
[0072] Comparative Example 1
[0073] Compared with Example 4, the difference lies in that the binder of the sodium ion battery is polyvinylidene fluoride (PVDF, model HSV900), and the following adaptive adjustments are made to the positive electrode paste of the sodium ion battery: the mass ratio of the doped sodium iron phosphate material, the conductive agent, and the binder is 9.0:0.4:0.6; the Dv10 of the doped sodium iron phosphate material used is 0.95 μm, Dv50 = 2.2 μm, Dv90 = 5.4 μm, and the specific surface area is 8.5 m 2 / g.
[0074] Comparative Example 2
[0075] Compared with Example 1, the difference lies in that the temperature of the free radical polymerization reaction is 85 °C.
[0076] Comparative Example 3
[0077] Compared with Example 1, the difference lies in that the temperature of the free radical polymerization reaction is 88 °C.
[0078] Comparative Example 4
[0079] Compared with Example 1, the difference lies in that the temperature of the free radical polymerization reaction is 92 °C.
[0080] Comparative Example 5
[0081] Compared with Example 1, the difference lies in that the temperature of the free radical polymerization reaction is 96 °C.
[0082] Performance Test
[0083] The weight average molecular weight of the binders of Examples 1-3 was measured by gel liquid chromatography, and the weight average molecular weight of the binders of Examples 1-3 was found to be in the range of 600,000 to 1,200,000.
[0084] Referring to the Dv50 particle size of the binders in Test Examples 1-3 by laser diffraction method for particle size distribution in accordance with GB / T 19077-2016, the Dv50 particle size of the binders in Test Examples 1-3 was measured to be 60-110 μm.
[0085] The solid content of the positive electrode slurries in Test Examples 4-6 and Comparative Example 1 was tested by the baking method. The binders in Comparative Examples 2-4 were used to prepare positive electrode slurries and sodium ion batteries according to the method of Test Example 4, and the solid content of the corresponding positive electrode slurries in Comparative Examples 2-4 was tested. The test results are shown in Table 1.
[0086] The tap density of Test Examples 4-6 and Comparative Examples 1-5 was tested by the surface density and thickness difference method. The test results are shown in Table 1.
[0087] Referring to GB-T2790-1995, the pole piece adhesion of Test Examples 4-6 and Comparative Examples 1-5 was tested. The test results are shown in Table 1. In this article, the pole piece adhesion is divided into three grades: "excellent", "good" and "general". "Excellent" means that there is no peeling between the coated surface of the pole piece and the current collector, "good" means that there is slight peeling between the coated surface of the pole piece and the current collector, and "general" means that the coated surface of the pole piece is completely peeled off from the current collector.
[0088] The specific capacity and capacity retention rate after 200 cycles of Test Examples 4-6 and Comparative Examples 1-5 were tested by the charge-discharge cycle test method. The test results are shown in Table 1. Among them, the formula for the capacity retention rate of the sodium ion battery after the 200th cycle is: (discharge capacity of the 200th cycle / first discharge capacity) × 100%.
[0089] Table 1 Performance test results of Test Examples 4-6 and Comparative Examples 1-5
[0090]
[0091] As can be seen from Table 1, compared with Comparative Example 1, using the binders in Test Examples 4-6 can increase the solid content of the slurry, and the test results of tap density, adhesion, specific capacity and capacity retention rate are also better than those of Comparative Example 1, indicating that the binder provided by the present invention is beneficial to increasing the solid content, improving the adhesion between the positive active material and the current collector, and increasing the specific capacity and cycle life.
[0092] From the test results of Test Example 1 and Comparative Examples 2-5, it can be seen that when the polymerization temperature exceeds 80 °C, the solid content will decrease, the tap density will become smaller, and the test results of pole piece adhesion, specific capacity and cycle performance will become worse.
[0093] The above are only exemplary embodiments of the present invention, and do not limit the patent scope of the present invention. Any equivalent structural transformation made by using the content of the specification of the present invention under the technical concept of the present invention, or direct / indirect application in other related technical fields, is included in the patent protection scope of the present invention.
Claims
1. A method for preparing an adhesive, characterized in that, It includes the following steps: Mix a first monomer, a second monomer, a solvent, and an initiator, and carry out a radical polymerization reaction to obtain a binder; wherein: The first monomer includes any one of styrene, methyl acrylate, butadiene, propylene, difluoroethylene, and tetrafluoropropylene, and the second monomer includes any one of tetrafluoroethylene, isobutene, vinyl ethyl ether, methyl methacrylate, methylstyrene, acrylonitrile, and hexafluoropropylene. At least one of the first monomer and the second monomer contains a polar group; The mass ratio of the first monomer to the second monomer is (6 - 8):(2 - 4).
2. The preparation method of the binder according to claim 1, characterized in that The conditions of the radical polymerization reaction include: the temperature is 60 - 80 °C, the pressure is 3 - 8 Mpa, and the time is 8 - 10 h.
3. The preparation method of the binder according to claim 1, characterized in that, The solvent includes at least one of deionized water, N,N-dimethylformamide, N-methylpyrrolidone, tetrahydrofuran, and pyridine; and / or, The mass ratio of the first monomer to the solvent is (6 - 8):9; and / or, The initiator includes any one of azobisisobutyronitrile, benzoyl peroxide, diisopropyl peroxydicarbonate, and di-tert-butyl peroxide; and / or, The mass ratio of the first monomer to the initiator is (6 - 8):
2.
4. The preparation method of the binder according to claim 1, characterized in that, The step of mixing the first monomer, the second monomer, the solvent, and the initiator and carrying out a radical polymerization reaction to obtain a binder includes: Mix the first monomer, the second monomer, the solvent, and the initiator, and carry out a radical polymerization reaction to obtain a slurry containing the binder; Filter the slurry containing the binder to obtain a solid; Wash and dry the solid to obtain a binder.
5. The preparation method of the binder according to claim 4, characterized in that, The solvent for washing is hydrofluoric acid or sodium hydroxide; and / or, The drying temperature is 60 - 80 °C.
6. An adhesive, characterized in that, The binder is prepared according to the preparation method of the binder according to any one of claims 1 to 5.
7. A positive electrode paste, characterized in that, The positive electrode slurry includes the binder according to claim 6.
8. The positive electrode paste according to claim 7, wherein, The positive electrode slurry further includes a positive electrode active material and a conductive agent, and the mass ratio of the positive electrode active material, the conductive agent, and the binder is (8.5 - 9.5):(0.3 - 2.0):(0.4 - 3.0).
9. A positive electrode plate, characterized in that, The positive electrode plate includes a positive electrode current collector and a positive electrode active layer provided on at least one surface of the positive electrode current collector, and the positive electrode active layer includes the positive electrode slurry according to claim 7 or 8.
10. A sodium-ion battery, characterized in that, The sodium ion battery includes the positive electrode plate according to claim 9.